Scarification and gibberellic acid in the germination and initial development of pindaiba (Duguetia lanceolata ST Hil) - Credo Assis, Kamila Cristina de [UNESP]; Geraldo, Guilherme Serra; Salatino Guardabaxo, Cintia Moda; Baquiao, Eunice Maria [UNESP]; Rezende, Bruna Nogueira [UNESP]; Resende Maciel, Anna Lygia de (Inst Federal Sul Minas Gerais-i Fsuldeminas, 2020)
Duguetia lanceolata St. Hill is a species native to the Atlantic Forest. Its seeds contain substances that have a germination inhibiting effect. In view of the above, the present work aimed to evaluate the influence of gibberellic acid and mechanical scarification on germination and seedling development of the D. lanceolata. This work was developed at IFSULDEMINAS - Campus Muzambinho, MG, Brazil. The seeds were obtained from fruits collected from adult plants. The experimental design was in randomized blocks, in a 5x2 factorial scheme with three replications with eighteen plants per plot. The treatments consisted of different concentrations of gibberellic acid (0, 5, 10, 15 and 20 mg L-1) and mechanical scarification (presence and absence). Leaf number, stem diameter and germination percentage were evaluated. The data were subjected to analysis of variance, the significant difference between treatments being determined by the F test and later, the qualitative variables were analyzed by the Scott-Knott test, and the quantitative variables by regression, both at the 5% level. The gibberellic acid and scarification do not influence the stem diameter and the number of seedling leaves. There was a linear increase in the percentage of germination with increasing doses of gibberellic acid up to the concentration 20.0 mg L-1 when scarification did not occur (35.19%). Quadratic behavior occurred with gibberellin doses when the seeds undergo mechanical scarification with a maximum dosage of 10.0 mg L-1 and corresponding germination of 42.59%. Mechanical scarification promoted an increase in germination when GA(3) was not applied, and at the dosage of 10.0 mg L-1.
Keywords: Annonaceae; GA(3); Radicle protrusion; Break dormancy